The Correspondence of the Equal Two-Component Phraseologies in Terms of Construction - Gulara, Aynazarova; Sharigul, Allaniyazova (International Journal of Membrane Science and Technology, 2023)
In the article, the grammatical compatibility of two-component phraseology that stands out as a different structure in the Karakalpak language is discussed with examples. Various grammatical formants connecting the lexemes in the composition of such phraseology are used in the form of repetitions or referring to the similarity. Correspondences in the creation of phraseology create strong harmony, and rhythm.